PEMANFAATAN SULING DIATONIK (SULING SUNDA) UNTUK MENGHITUNG FREKUENSI DAN CEPAT RAMBAT BUNYI DI UDARA MENGGUNAKAN SOFTWARE AUDACITY DAN KETERKAITANNYA TERHADAP ASPEK KESEHATAN - Pebralia, Jesi - (Jurnal Inovasi Pendidikan, 2019)
This study aims to determine the value of frequency and speed of sound propagation in the air by using diatonic flutes and audacity software. In addition in this study,  analysis of the relationship of frequency to health aspects were included. In this study there are two kind the research of methods, experimental method and literature study. The experimental method is used to obtain frequency and the speed of sound propagation data in the air using diatonic flute (Sundanese flute) and pentatonic flute (modern flute) as a comparison and measured using Audacity software. Literature study is used to find references about theories and or facts that explain the relationship between rhythmic sounds to the aspects of human health. The results showed that: 1) the frequency produced by the diatonic flute was in the range of 649 Hz - 753 Hz, 2) the average value of speed of sound propagation in the air was measured using a diatonic flute (Sundanese flute) of 291,472457 m / s, 3 ) the diatonic flute frequency (Sundanese flute) is greater than the pentatonic flute (modern flute), 4) the frequency that can be utilized in the health field is sound with low to medium frequency, which is in the range of 750-3000 Hz so that the sound produced by the diatonic flute has an impact which is good for improving health.